Analisis Efektivitas Dan Tinjauan Audit Syariah Dalam Pelaksanaan Dan Pengawasan Kepatuhan Syariah Pada Bank Syariah - Evony Silvino Violita; Gustining Handarbeni (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2017)
This study aims to analyze the implementation procedures and supervision of Sharia compliance conducted by the Sharia Supervisory Board (DPS) as well as its relationship with the internal role of the bank and the review of sharia audit over the implementation process. The method used in this research is the interview with the PT Bank Syariah Z. From the results of this study found that DPS has an important role in monitoring the implementation and supervision of Shariah compliance conducted with the control of preventive (ex-ante) and curative (ex-post ). There is a risk in the implementation of DPS working procedures where the work of DPS is assisted by the Sharia Compliance Officer who also has a position as an internal bank employee that can reduce the independence of the sharia audit process by DPS. The results of this study have implications on the need for regulators to review and build a system of supervision of sharia where the process of supervision can be more effective by not causing a significant increase in cost so as not to reduce the competitiveness of sharia banking in Indonesia.